1993
DOI: 10.1007/bf00016621
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acetylene on N transformations in an acid oak-beech soil

Abstract: The effectiveness of acetylene (C2H2) as inhibitor of nitrification was studied in relation to the decomposition of C2H 2. This was done by examining the effects of single and multiple additions of different C2H 2 concentrations (10, 100, 1000 Pa) on mineral N and NO~-N production in samples of the organic (FH) and upper mineral (Ah) layer of an acid oak-beech forest soil. The decomposition of C2H 2 was much faster in Ah samples than in FH samples. A single addition of 10 Pa C2H 2 was not sufficient for comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
(14 reference statements)
0
17
0
Order By: Relevance
“…In accordance with effective concentrations of CO that completely inhibited the reduction of C 2 H 2 to C 2 H 4 [18] , the addition of 0.5 KPa C 2 H 2 and in combination with 5.0 KPa CO in the headspace, was used to separately measure in situ CH 4 and C 2 H 4 production in the pine forest stand. Based on the in situ measurement of CH 4 production using only 0.5 kPa C 2 H 2 , there was a significant increase in CH 4 concentration inside each chamber within 3 h upon C 2 H 2 addition (P≤0.05) (Figure 3), and 15 h afterwards CH 4 concentration started to reduce with time due to rapid decomposition of C 2 H 2 [18,20] . This phenomenon indicated that in situ CH 4 production in upland forest soils could be measured only within several hours upon C 2 H 2 addition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with effective concentrations of CO that completely inhibited the reduction of C 2 H 2 to C 2 H 4 [18] , the addition of 0.5 KPa C 2 H 2 and in combination with 5.0 KPa CO in the headspace, was used to separately measure in situ CH 4 and C 2 H 4 production in the pine forest stand. Based on the in situ measurement of CH 4 production using only 0.5 kPa C 2 H 2 , there was a significant increase in CH 4 concentration inside each chamber within 3 h upon C 2 H 2 addition (P≤0.05) (Figure 3), and 15 h afterwards CH 4 concentration started to reduce with time due to rapid decomposition of C 2 H 2 [18,20] . This phenomenon indicated that in situ CH 4 production in upland forest soils could be measured only within several hours upon C 2 H 2 addition.…”
Section: Discussionmentioning
confidence: 99%
“…Within three hours after C 2 H 2 addition, there was a significant accumulation of CH 4 and C 2 H 4 in the headspace inside each chamber (P≤0.05) (Figure 3, Table 2), and 15 hours afterwards CH 4 concentrations began to decrease with time and C 2 H 4 concentrations decreased to zero. Acetylene concentrations in the vials 15 h after coverage also decreased to zero (data not shown), due to rapid decomposition of CO [21] and C 2 H 2 [18,20] . Hence, a long-term incubation (e.g.…”
Section: In Situ C 2 H 4 and Ch 4 Production In N-fertilized Temperatmentioning
confidence: 90%
See 1 more Smart Citation
“…It strongly suggests that at less than 1 kPa C,H,, the increase in N,O production could be partly attributed to denitrification under the experimental conditions. Low doses of C,H, (normally within a range of 10 to 100 Pa) inhibit autotrophic NH,' oxidation without affecting other N transformation processes (Bremner and Blackmer 1979;Boer et al 1993;Inubushi et al 1996). The efficiency of this inhibition in the aerobically incubated forest soils may be weakened because of the microbial decomposition of C,H,, especially in surface mineral forest soils (Boer et al 1993), and hence the presence of 10 Pa C,H, was not sufficient for the complete inhibition of autotrophic nitrification under the experimental conditions (Fig.…”
Section: Effect Of Chconcentrations On Soil N Forms and No Productionmentioning
confidence: 99%
“…Thus, 100 Pa C,H, in the headspace cannot be used to study gaseous N loss potentials from the aerobically incubated forest soils. Using the single and multiple (once every week) addition of C,H,, Boer et al (1993) showed that the decrease of net N mineralization by C,H, occurred in the uppermost mineral layer of an acid oak-beech forest soil, and this reduction was increased with increasing concentrations of C,H, within a range from 10 to 1,000 Pa C,H,. However, they did not simultaneously measure the variations of microbial biomass N contents in soil.…”
Section: Effect Of Chconcentrations On Soil N Forms and No Productionmentioning
confidence: 99%